Praefatio - Preface - Marciniak, Katarzyna (Ciceroniana On Line, 2020)
For many of us this congress was the last such event before the outbreak of the coronavirus pandemic in February 2020. Our meeting concluded with an optimistic message of hope, but this was not the kind of hope that would make us nimis creduli postero. Studies of Cicero’s turbulent life and the stormy biographies of our Ciceronian Mentors in many parts of the world, who – like Morawski, Zieliński, and Kumaniecki – for various reasons could not enjoy negotium sine periculo et otium cum dignitate, fortify a hope that is not vain but results from the steadfast commitment to share artes liberales as actual tools of dialogue and integration. In the upcoming months of 2020 it was, and still is, a precious source of strength for our community. May the readers of this volume, who also belong to this millenia-old community linked by the ties of artes liberales, truly feel the hope that emanates from between the lines of the research papers and discussions gathered here, just as we found it emanating from the works of Cicero.